Who's afraid of the dark? - Bonsall, Crosby Newell, 1921- (New York : Harper & Row, 1985)
A small boy projects his fear of the dark onto his dog.
Elementary School Library Collection (Bro-Dart).
Horn Book Magazine.
Children's Catalog (Wilson).
K-3.
1.6
13 20 21 25 26 36 39
Keywords: Night -- Fiction